Ш.СЕЙИТОВ РОМАНЛАРЫНЫҢ КӨРКЕМ ТИЛ ӨЗГЕШЕЛИГИ - Каниязова, Ж.О. (SCIENCE and SOCIETY, 2016)
The object of the research in the article is Sh. Seitov‘s novels. Normally, a unique literary language characterizes the writer‘s works.The author of the article shows the originality of the writer‘s novels by analyzing dialogues, monologues and the lexical layer of his works.
Keywords: novel; artistic speech; image; personage; character; the character of the hero; plot; dialogue; artistic vocabulary; nickname of the hero